1991
DOI: 10.1093/bja/66.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Subhypnotic Doses of Thiopentone and Propofol Cause Analgesia to Experimentally Induced Acute Pain

Abstract: Subhypnotic doses of thiopentone are considered to have a hyperalgesic effect, while propofol has a hypoalgesic effect. We investigated the effect of these drugs on the nociceptive system by measuring the pain threshold to laser stimulation and the pain evoked potential (power and latency). Nineteen patients (ASA group I) participated. Twelve patients received thiopentone 0.5 mg kg-1 and propofol 0.25 mg kg-1 in random order separated by an interval of 14 h, and seven patients received saline. Immediately afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…While few studies observed analgesic effect and reduction of postoperative opioid requirement after propofol anesthesia when compared to volatile anesthetic anesthesia [197], others showed no effects on analgesia [198] or even enhanced pain sensitivity [199]. Patients who had general anesthesia with isoflurane or sevoflurane were found to report more postoperative pain and require more morphine than those anesthetized with propofol [200, 201].…”
Section: ) Propofol and Pain Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…While few studies observed analgesic effect and reduction of postoperative opioid requirement after propofol anesthesia when compared to volatile anesthetic anesthesia [197], others showed no effects on analgesia [198] or even enhanced pain sensitivity [199]. Patients who had general anesthesia with isoflurane or sevoflurane were found to report more postoperative pain and require more morphine than those anesthetized with propofol [200, 201].…”
Section: ) Propofol and Pain Modulationmentioning
confidence: 99%
“…Patients who had general anesthesia with isoflurane or sevoflurane were found to report more postoperative pain and require more morphine than those anesthetized with propofol [200, 201]. Also, sub-hypnotic doses of propofol were found to increase the pain threshold in human pain models to laser stimulation and decreased the amplitude of pain-evoked potential significantly [197]. In contrast, prospective blind randomized trial reported no difference or even less analgesia among patients anesthetized with propofol compared with volatile anesthetics [202, 203].…”
Section: ) Propofol and Pain Modulationmentioning
confidence: 99%
“…Quite naturally, investigators studied its effects on pain perception and, just like early reports on barbiturates, noted hyperalgesic action associated with propofol both in preclinical, experimental as well as clinical studies. 12,14,16,42,43 However, despite these reports, the use of propofol as analgesic drug remained a topic of discussion. The notion that propofol was used to treat inadequate analgesia in a scientific report in 1999 44 prompted the following commentary: “Too often, in our opinion, patients receive propofol, at a time when an analgesic would serve them better.…”
Section: Discussionmentioning
confidence: 99%
“… ++ sehr ausgeprägt, + vorhanden, o kein Effekt. a Sanders et al [41] konnten einen antinozizeptiven Effekt an Ratten feststellen. b Anker-Møller et al [4] konnten einen analgetischen Effekt bei Probanden aufzeigen. …”
Section: Figures and Tablesunclassified